2003
DOI: 10.1103/physrevb.68.054502
|View full text |Cite
|
Sign up to set email alerts
|

Hole doping in Pb-free and Pb-substituted(Bi,Pb)2Sr2

Abstract: Using single-phase samples of the (Bi,Pb) 2 Sr 2 Ca 2 Cu 3 O 10ϩ␦ ͓͑Bi,Pb͒-2223͔ high-T c superconductor and utilizing two complementary analysis techniques, i.e., coulometric redox titration and x-ray-absorption nearedge structure spectroscopy at both O K and Cu L edges, the individual charges of the (Bi,Pb) 2 O 2ϩ␦ charge reservoir and the superconductive block that contains the three CuO 2 planes are consistently determined. Lead is found to enter the ͑Bi,Pb͒-2223 phase with a valence close to III on averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 34 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…If there are holes present in the system due to the As diffusion, then the ground state for Cu L 3,2 -edge will also consist of the configuration 3d 9 L (Cu 2 þ plus an oxygen p hole). The peak B at an energy of 934.4 eV is an indication of the hole doping and is assigned to the transition 3d 9 L-2p3d 10 L. A similar feature is reported by van der Laan et al [21] in the L 3,2 -edge of CuO at 935 eV due to the presence of defect state 3d 9 L in the ground state and is therefore assigned to the transition 3d 9 L-2p3d 10 L. This assignment is in accordance with other reports on high-T c Cu-based superconductors [22][23][24][25] and Cu-doped GaN nanowires [26], where a similar feature is reported to be an indication of the hole-doping in the system. Sarma et al [22] argued the presence of holes in the high-T c superconductor YBa 2 Cu 7 O 7Àd based on the presence of a similar peak at 933 eV which appears as a shoulder to the main L 3 -edge.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…If there are holes present in the system due to the As diffusion, then the ground state for Cu L 3,2 -edge will also consist of the configuration 3d 9 L (Cu 2 þ plus an oxygen p hole). The peak B at an energy of 934.4 eV is an indication of the hole doping and is assigned to the transition 3d 9 L-2p3d 10 L. A similar feature is reported by van der Laan et al [21] in the L 3,2 -edge of CuO at 935 eV due to the presence of defect state 3d 9 L in the ground state and is therefore assigned to the transition 3d 9 L-2p3d 10 L. This assignment is in accordance with other reports on high-T c Cu-based superconductors [22][23][24][25] and Cu-doped GaN nanowires [26], where a similar feature is reported to be an indication of the hole-doping in the system. Sarma et al [22] argued the presence of holes in the high-T c superconductor YBa 2 Cu 7 O 7Àd based on the presence of a similar peak at 933 eV which appears as a shoulder to the main L 3 -edge.…”
Section: Resultssupporting
confidence: 83%
“…Seong et al found similar structure at an energy of around 934.5 eV and attributed it to the presence of Cu 3 þ [26]. It has been used to quantitatively determine the hole concentration in the system [24,25]. Following the procedure reported in the literature, peak A was fitted with a combination of Lorentzian and Gaussian functions and the small peak B with a Gaussian function.…”
Section: Resultsmentioning
confidence: 99%
“…This situation is parallel to that known for a related cuprate system, ðBi; PbÞ 2 Sr 2 Ca 2 Cu 3 O 10þd ; for which 15% Pb-for-Bi substitution was found to decrease the oxygen content from d ¼ 0:28 to 0.19[33]. Here, for our (Bi 1.7 Pb 0.4 )Sr 2.15 Co 2 O 8+d sample the oxygen content was determined at d ¼ 0:22 (cerimetry)/0.26 (iodometry) (Table 2).…”
mentioning
confidence: 54%
“…This is again a parallel situation to that known for ðBi; PbÞ 2 Sr 2 Ca 2 Cu 3 O 10þd [33], but not straightforwardly expected from the Hall coefficient and resistivity data previously reported for the [((Bi,Pb)O 17o ) x ] 2 [(SrO 17e ) y ] 2 CoO 2 system [28,32]. That is, in this system the Pb-for-Bi substitution slightly decreases the magnitude of the Hall coefficient and enhances metallic behaviour (though the enhancement was found more pronounced for the out-of-plane than the in-plane resistivity).…”
Section: Oxygen Content and Valence Of Cobalt: Wet-chemical Analysismentioning
confidence: 83%
“…From these reasons we have chosen a more straightforward way by analysing the Cu L 3 -absorption edge. This method has been used for LSCO [9,10] and n = 2 [11][12][13] and n = 3 [14] Bi-based cuprates and is a direct measure of the carrier concentration in the CuO 2 -planes.…”
Section: Introductionmentioning
confidence: 99%